THE LANGUAGE SHIFTING IN MUNA LANGUAGE (A Study of Munanese at Pondidaha Sub-District) - Fitri, Wa Ode (Universitas Halu Oleo, 2019)
This research discusses the language shifting in Muna language for Munanese who lived inAhuawatu village, Pondidaha Sub-District, Konawe Regency. Language contact that has occurred at multilingual society in Ahuawatu became an interesting phenomenon to be learnt, because it has close relationship with the use of ethnic language of the residents in this village. This study focuses on the condition of language shifting of Muna language to Java language, and the causes that lead the shift of language for Munanese. The main data of the research was taken in Ahuawatu village. Observation and interview were used by the researcher in collecting the data from five informants in this area. The result of this research showed the condition of Muna language in Ahuawatu has begun to shift for parental age, and dominantly shifted for their children. It indicated from their habits which use Java language step by step in their daily life as a Munanese. The causes of language shift in parental age are the power of Java language, the number of speaker, and intercultural marriage. While the shift of Muna language to their children are caused by the use of Muna language in family domain, also the maintaining process of Muna culture in family domain.Â Keywords: Language shift, Munanese, Muna Language, Java Language.